Health Promotion Strategies in Integrated Healthcare Program Park of Public Health Center - Kurniawan Edi Priyanto; Sutrisno Sutrisno; Mohammad As'ad Effendy (Universitas Airlangga, 2020)
Introduction: One form of community empowerment effort in the field of health is to develop an Integrated Healthcare Program. Integrated Healthcare Program Park in East Java quantitatively until the year 2014 has exceeded as many as 12,227 or an increase of 22.27% from the declaration of movement activities of 10,000 starting from 2012. However, qualitatively in that year there were only 23% in the optimal category. To optimize function of Integrated Healthcare Program Park it is necessary to have a Companion Officer in the monitoring and assisting cadres. This study is to know the implementation of health promotion strategy in Integrated Healthcare Program Park at Public Health CenterMethods: Data were collected by in-depth interviews. Implementation of empowerment activities found the training of companion officers and cadres are uneven.Results: Activity of developing the social support found the existence of problems because of the absence of early child development cadres and insufficient means of educational game tools. Advocacy activities conducted policy proposals on the establishment of early child development cadres.Conclusion: Partnership activities have created a good coordination between companion officers with the stakeholders, but there are problems in the mechanism of distributing incentives for companion officers and cadres.